Al-hurriyyah fi al-asr : (Dar Mirit, 2006)
'Freedom in captivity : the crisis of political reform and civil rights' Cover- and spine title reads: Al-hurriyyah fi al-asr : ma'zaq al-islah al-siyasi wa al-muwatanah / 'Freedom in captivity : the crisis of political reform and citizenship' Politics.